The Influence of Service Quality, Product Quality and Price Perception on Purchasing Decisions Through Customer Satisfaction At The Local Part of PT Sumber Mas Indah Plywood - saftri, eka rizky; alkusani, Alkusani; Basyari, Alif Sulthon (INNOVATION RESEARCH JOURNAL, 2025)
The purpose of this research is to determine the influence of product quality and price perception on purchasing decisions through customer satisfaction at PT. Local Source of Mas Indah Plywood. This research is quantitative descriptive research. The research was conducted at PT. Sumber Mas Indah Plywood Plywood Solution division. The sample in this study amounted to 190 respondents. Sampling used purposive sampling technique and the analytical tool used was Path Analysis, which was previously carried out by classical assumption tests. The data collection technique was carried out using the questionnaire method. Data analysis using SPSS 25. The results of hypothesis testing using the t test partially show that service quality, product quality and price perception influence customer satisfaction and purchasing decisions. In the analysis of the coefficient of determination, an Adjusted R Square value of 0.920 was obtained, indicating that 92% of customer satisfaction can be explained by the two independent variables in the regression equation, while the remaining 8% is explained by variables outside the research model. and the Adjusted R Square value is 0.979, which shows that 97,9% of purchasing decisions can be explained by the two independent variables in the regression equation. Meanwhile, the remaining 2,1% is explained by variables outside the research model.